Bendung Argoguruh 1935 dan Potensinya sebagai Sumber Pembelajaran Sejarah di Lampung - Kian Amboro (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
In 1905 the Dutch East Indies Government began implementing an Ethical Policy in Lampung. Of the three policies, the most visible traces in Lampung are the policy of population movement and irrigation development. This study aims to: (1) explain the history of the existence of the 1935 Argoguruh Dam in Tegineneg, Lampung. (2) analyzing the potential aspects of the 1935 Argoguruh Dam in Tegineneng, Lampung as a source of historical learning, especially local history. This research uses a qualitative descriptive approach with historical data collection methods and observation methods. The results show that (1) Argoguruh Dam 1935 is a river catchment building as part of an irrigation system that functions to irrigate agricultural land that has been moved from the densely populated island of Java to the still rare island of Sumatra its inhabitants (2) the potential aspects of the Argoguruh Dam 1935 as a source of historical learning include, (a) the contextual historical aspect, (b) the aspect of the building as a historical heritage, (c) the character values that can be developed in history learning.